Simulation of segregation in continuous casting of high-carbon Fe-C alloys. (1st January 2002) - Bozzine, B.; Serra, M.; Fanigliulo, A.; Antonetti, L.; Boniardi, M.
In this paper, we propose a mathematical model devised to simulate the segregation profile on a cross-section of a high-carbon steel bloom produced by continuous casting, as a function of the operation conditions of the plant (withdrawal speed, superheat and coolant flow). The model consists of two coupled routines simulating the thermal and segregation behaviour of the system. The segregation routine is innovative, because (i) it simulates the segregation process accurately, and (ii) it can be used for on-line simulation of the behaviour of an industrial continuous casting process. In order to reduce the computational problem to a manageable degree of complexity, the physics of the process can be modelled with two time-dependent parameters describing (i) convective effects on the distribution of the solute (homogenisation parameter χo); (ii) displacements from thermodynamic equilibrium brought about by mass transport at the solid-liquid interface (effective partition coefficient κPe), a function of the total liquid fraction χi, tot through the local thermal gradient ΔT). The numerical model is 2-D, but 3-D information is conveyed by the parameters χo); and κPe. The mathematical model includes the flowing balances energy, mass, species and momentum; the overall system can be simplified by including convective effects through the time-and space-dependent homogenisation parameter χo. The number of equations is matched to the number of unknowns by correlating the liquid phase composition with the temperature through the linearised equilibrium Fe-C phase diagram. The results of the numerical simulation of the segregation profile are in good agreement with the experimental data available in the literature; the results of the thermal simulation are in excellent agreement with experimental data obtained in this work.